2023
DOI: 10.3389/fcell.2023.1145702
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous administration of microplastics and cadmium alters rat testicular activity and changes the expression of PTMA, DAAM1 and PREP

Abstract: This paper confirms the damaging effects produced by MP and Cd on testicular activity in the rat. Oral treatment with both chemicals resulted in testicular damage, documented by biomolecular and histological alterations, particularly by impaired morphometric parameters, increased apoptosis, reduced testosterone synthesis, and downregulation of the steroidogenic enzyme 3β-HSD. We also demonstrated, for the first time, that both MP and Cd can affect the protein level of PTMA, a small peptide that regulates germ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…As expected, results showed that 40 days of Cd treatment provoked a significant reduction in RSPH6A level in both the testis and SPZ. This data further confirms the detrimental action of Cd, which alters testicular activity at various levels, including steroidogenesis, 27,43 blood-testis barrier integrity, 19,21 cytoarchitecture of the cells composing the seminiferous epithelium, 18,25,26 and sperm parameters, especially motility. 8,21 Interestingly, the antioxidant ability of Mlt to counteract the Cd-induced effect was evidenced again, as only a slight decrease in RSPH6A expression was observed in the group treated simultaneously with Mlt and Cd.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As expected, results showed that 40 days of Cd treatment provoked a significant reduction in RSPH6A level in both the testis and SPZ. This data further confirms the detrimental action of Cd, which alters testicular activity at various levels, including steroidogenesis, 27,43 blood-testis barrier integrity, 19,21 cytoarchitecture of the cells composing the seminiferous epithelium, 18,25,26 and sperm parameters, especially motility. 8,21 Interestingly, the antioxidant ability of Mlt to counteract the Cd-induced effect was evidenced again, as only a slight decrease in RSPH6A expression was observed in the group treated simultaneously with Mlt and Cd.…”
Section: Discussionsupporting
confidence: 75%
“… 15 Among the environmental substances directly involved in growing infertility, Cd is a heavy metal with a very long half‐life 16 that acts as an endocrine disruptor 17 , 18 and induces oxidative stress. 19 , 20 , 21 , 22 Cd deleterious effects on health and on the fertility rate are widely studied, 23 since Cd impairs spermatogenesis, 18 , 21 , 24 , 25 , 26 , 27 finally leading to a reduction in sperm quantity and quality, specifically by reducing SPZ motility. 28 , 29 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the whole spermatogenic process, including the events that occur in the dynamics of BTB and GC transit through the lumen, is regulated by T (Venditti, Romano, et al, 2021). T biosynthesis is catalyzed by specific sets of steroid enzymes, such as StAR and 3β‐HSD, which are sensitive to external environmental pollutants (Venditti et al, 2021a; Venditti, Romano, et al, 2021; Venditti et al, 2023). Rapa has been shown to increase T levels that are reduced by silencing the zinc transporter family 4 ( ZnT4 ) gene through the phosphatidylinositol 3‐kinase/Akt/mTOR autophagy pathway in TM3 mouse Leydig cells (Li et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Cell differentiation during spermatogenesis requires a proper cytoskeleton dynamic, regulated by several proteins [ 24 ], such as prolyl endopeptidase (PREP) and disheveled-associated activator of morphogenesis 1 (DAAM1), which play key roles in the postnatal development of the rat testis [ 25 , 26 ] and, as for PREP, in sperm motility [ 27 , 28 ]. Moreover, as we have found their altered expression and localization in pathological and/or altered spermatogenesis [ 29 , 30 , 31 , 32 ], we raised the possibility of their use as potential new markers of proper fertility. Specifically, PREP is a binding partner of tubulin [ 25 ]; it also directly limits GnRH stimulation of the pituitary gonadotropes by cleaving its C-terminal glycinamide residue, as demonstrated in rat and ovine hypothalamic extracts [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%